Efektivitas Rancangan Program Pengembangan Self Awareness Berbasis Teknologi Informasi dalam Meningkatkan Kemampuan Mengenal Emosi (Studi pada Peserta Didik Kelas XI di SMK Negeri 1 Painan) - Okta Jumelda Putri; Helma Helma; Rahma Wira Nita (Departement of Mathematics Education, 2023)
This research is motivated by the phenomenon of students who have not the ability to recognize their emotions.The aims of this study were: (1) Profile of self-awareness of students before treatment, (2) Profile of self-awareness of students after treatment, (3) The effectiveness of thedevelopmental program counseling based on information technology (IT) to improving their ability to recognize emotions. This study uses a quantitative approach, by types of experimental research. The location of this research is at SMK Negeri 1 Painan. The samples in this study were 30 students in class XI OTKP 1 (experimental group) and 30 students in class XI PHT 1 (control group). The data collected questionnaire technique, and was analyzed by Ancova technique. The research finding : 1) The level of self-awareness before treatment was classified as low, both in the experimental class and the control class. 2) The level of Self Awareness after the treatment underwent significant changes, especially in the experimental group. 3) Program developmental counseling based on information technology (IT) effective to significantly to increasing students ability self awareness. Based on research finding, it is recommended to the counselor to using a guidelines developmental program counseling to improving students' ability self awareness